Aplikasi Logika Fuzzy untuk Penentuan Beasiswa Peningkatan Prestasi Akademik Menggunakan Metode Fuzzy Mamdani Pada ITB Indonesia - Raheliya Br Ginting, Rahel; Sinuhaji, Nirwan; Dewi, Siti Indriyastri; Ginting, Meiliyani Br (LPPM UNIKA Santo Thomas Medan, 2021)
The Indonesian Institute of Technology and Business is an institution engaged in the field of Education. Scholarship is a gift in the form of an award or in the form of financial assistance given to people who have achievements that aim to be used as a continuation of education that will be taken during education. In addition, scholarships are also given to students as an appreciation or support for outstanding students. This research was made with the aim that the Right Target, Right Amount and Timely scholarship program can be implemented in determining scholarships to improve academic achievement at the Indonesian Institute of Technology and Business. Based on the existing problems, the authors analyze and design an application system built using Matlab software by combining fuzzy logic and Matlab GUI.